PENGARUH PENGGUNAAN TEKNOLOGI DAN PENERAPAN E-COMMERCE TERHADAP PENINGKATAN PENJUALAN UMKM DI MASA PANDEMI COVID-19 - Pratiwi Nila Sari (Jurnal Ilmiah Akuntansi dan Manajemen, 2023)
The purpose of this study was to determine the influence of the use of technology and the application of e-commerce to the increase in sales of MSMEs during the Covid-19 pandemic in Bekasi Regency. The data analysis methods used in the study were 1) data quality test consisting of Validity test and Reality test, 2) Classical Assumption Test consisting of Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test, 3) Multiple Linear Regression Test, 4 ) Hypothesis Testing which consists of Coefficient of Determination Test (R2), Simultaneous Test (F Test), and Partial Test (t Test). The results showed that the use of technology individually/partially had no effect on increasing sales of MSMEs in Bekasi Regency. While the results of the application of e-commerce individually / partially affect the increase in sales of MSMEs in Bekasi Regency. For the third hypothesis, it is proven that the use of technology and the application of e-commerce together has an effect on increasing sales of MSMEs in Bekasi Regency.